2016
DOI: 10.1016/j.jfoodeng.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying technique and feed flow rate on bacterial survival and physicochemical properties of a non-dairy fermented probiotic juice powder

Abstract: Drying of probiotic fruit juice can be a good alternative for new probiotic foodstuff production since most probiotic foods are dairy-based products, which are not suitable for people with galactosemia, lactose intolerance or allergy to milk protein. Thus, the aim of this study was to evaluate the influence of spray and spouted bed drying and feed flow rate on the microorganism survival and physicochemical properties of probiotic orange juice powder. Fermented probiotic orange juice containing Lactobacillus ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 55 publications
3
32
0
1
Order By: Relevance
“…Barbosa et al [118] and Pereira et al [122] when producing orange and cashew apple juice powders, respectively, with lactic acid bacteria (LAB) verified that the powders stored at 4 ∘ C presented higher survival rates than at room temperature. Furthermore, the highest level of probiotic bacteria was observed for the orange juice powders produced at the lowest feed flow rate (0.2 L h −1 ), probably due to their low water contents [117]. However, these results were different to Mestry et al [126], who when preparing Production of chestnut mousse (pilot-scale anhydrous formulation) and sensory analysis [124] 16…”
Section: Dehydrated Foods With Probioticsmentioning
confidence: 90%
See 3 more Smart Citations
“…Barbosa et al [118] and Pereira et al [122] when producing orange and cashew apple juice powders, respectively, with lactic acid bacteria (LAB) verified that the powders stored at 4 ∘ C presented higher survival rates than at room temperature. Furthermore, the highest level of probiotic bacteria was observed for the orange juice powders produced at the lowest feed flow rate (0.2 L h −1 ), probably due to their low water contents [117]. However, these results were different to Mestry et al [126], who when preparing Production of chestnut mousse (pilot-scale anhydrous formulation) and sensory analysis [124] 16…”
Section: Dehydrated Foods With Probioticsmentioning
confidence: 90%
“…Good results have been obtained with freeze drying, as stated by Vikram Simha et al [113] and Barbosa et al [116], when producing probiotic pomegranate and orange powders, respectively. Spouted bed drying has also been used in some works because lower temperatures are applied [117] when compared to spray drying. Alves et al [117] observed that spouted bed orange juice dried samples presented higher viable microbial cell counts than the spray-dried ones; however, the last ones showed lower values of moisture content and water activity.…”
Section: Dehydrated Foods With Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…That result probably occurred because the high feed flow rate reduces the microencapsulation process time and the cell exposure to the high air inlet temperature. Thus, the process conditions provide the highest microbial viability using spray drying (Alves et al, 2016). Serantoni et al (2012) also confirmed that high aspiration rate directly positively influenced the contact time of the granulated material with the cyclone hot air in the drying chamber.…”
Section: Box-behnken Experimental Design Of the Spray Drying Conditionsmentioning
confidence: 60%